Sarcopenia and preserved bone mineral density in paediatric survivors of high‐risk neuroblastoma with growth failure. Issue 4 (29th June 2021) - Guo, Michelle; Zemel, Babette S.; Hawkes, Colin P.; Long, Jin; Kelly, Andrea; Leonard, Mary B.; Jaramillo, Diego; Mostoufi‐Moab, Sogol
Abstract: Background: Survival from paediatric high‐risk neuroblastoma (HR‐NBL) has increased, but cis ‐retinoic acid ( cis ‐RA), the cornerstone of HR‐NBL therapy, can cause osteoporosis and premature physeal closure and is a potential threat to skeletal structure in HR‐NBL survivors. Sarcopenia is associated with increased morbidity in survivors of paediatric malignancies. Low muscle mass may be associated with poor prognosis in HR‐NBL patients but has not been studied in these survivors. The study objective was to assess bone density, body composition and muscle strength in HR‐NBL survivors compared with controls. Methods: This prospective cross‐sectional study assessed areal bone mineral density (aBMD) of the whole body, lumbar spine, total hip, femoral neck, distal 1/3 and ultradistal radius and body composition (muscle and fat mass) using dual‐energy X‐ray absorptiometry (DXA) and lower leg muscle strength using a dynamometer. Measures expressed as sex‐specific standard deviation scores (Z‐scores) included aBMD (adjusted for height Z‐score), bone mineral apparent density (BMAD), leg lean mass (adjusted for leg length), whole‐body fat mass index (FMI) and ankle dorsiflexion peak torque adjusted for leg length (strength‐Z). Muscle‐specific force was assessed as strength relative to leg lean mass. Outcomes were compared between HR‐NBL survivors and controls using Student's t‐ test or Mann–Whitney U test. Linear regression models examined correlations between DXA and dynamometer outcomes. Results: We enrolled 20 survivors of HR‐NBL treated with cis ‐RA [13 male; mean age: 12.4 ± 1.6 years; median (range) age at therapy initiation: 2.6 (0.3–9.1) years] and 20 age‐, sex‐ and race‐matched controls. Height‐Z was significantly lower in HR‐NBL survivors compared with controls (−1.73 ± 1.38 vs. 0.34 ± 1.12, P < 0.001). Areal BMD‐Z, BMAD‐Z, FMI‐Z, visceral adipose tissue and subcutaneous adipose tissue were not significantly different in HR‐NBL survivors compared with controls. Compared with controls, HR‐NBL survivors had lower leg lean mass‐Z (−1.46 ± 1.35 vs. − 0.17 ± 0.84, P < 0.001) and strength‐Z (−1.13 ± 0.86 vs. − 0.15 ± 0.71, P < 0.001). Muscle‐specific force was lower in HR‐NBL survivors compared with controls ( P < 0.05). Conclusions: Bone mineral density and adiposity are not severely impacted in HR‐NBL survivors with growth failure, but significant sarcopenia persists years after treatment. Future studies are needed to determine if sarcopenia improves with muscle‐specific interventions in this population of cancer survivors.